Apakah Keberadaan Mass Rapid Transit Berdampak terhadap Transjakarta? Studi Kasus Transportasi Publik di DKI Jakarta - Salafi Nugrahani; Muhammad Halley Yudhistira (Jurnal Ekonomi & Kebijakan Publik, 2020)
Since 2004 the Provincial Government of DKI Jakarta has operated Transjakarta public transportation and began operating new publictransportation named Mass Rapid Transit (MRT) in 2019. However, the existence of the two modes still leaves some challenges in its setup. Currently, some of the Transjakarta operational areas intersect with the MRT operational areas within the same region. Inaddition, the Transjakarta modal setup is still constrained by physical integration with the new MRT mode since only two Transjakartabus stops have direct accessibility and connectivity with MRT stations in one transit area. This study aims to see the relationshipbetween the number of Transjakarta passengers with the existence of a new MRT mode, although currently Transjakarta is still constrained by physical integration with the MRT. This study also aims to see the complementary relationship when there is an increase in MRT ticket prices to a decrease in the number of Transjakarta passengers through the cross price elasticity approach. Testing this relationship is carried out using daily data at the bus stop level through the panel data regression method with a Fixed Effect Model approach. The estimation results show that the existence of the MRT is related to an increase in the number of Transjakarta passengers by 36.5 percent at Transjakarta stops which are within a 250 meter radius of the MRT station. However, this study has not found sufficient evidence of a complementary relationship related to the increase in MRT ticket prices to the decrease in the number of Transjakarta passengers.Keywords: cross price elasticity, fixed effect, Mass Rapid Transit (MRT), Transjakarta, transportationAbstrakSejak tahun 2004 Pemerintah Provinsi DKI Jakarta telah mengoperasikan moda transportasi publik Transjakarta dan mulaimengoperasikan moda transportasi publik baru berupa Mass Rapid Transit (MRT) pada tahun 2019. Akan tetapi, keberadaan keduamoda masih menyisakan beberapa tantangan dalam penataannya. Saat ini, sebagian wilayah operasional Transjakarta bersinggungandengan wilayah operasional MRT dalam lingkup area yang sama. Selain itu, penataan moda Transjakarta juga masih terkendalaintegrasi fisik dengan moda baru MRT karena hanya dua halte Transjakarta yang memiliki aksesibilitas dan konektivitas langsungdengan stasiun MRT dalam satu kawasan transit. Penelitian ini bertujuan melihat hubungan jumlah penumpang Transjakarta terhadap keberadaan moda baru MRT meski saat ini Transjakarta masih terkendala integrasi fisik dengan MRT. Penelitian ini juga bertujuan  melihat hubungan komplementer ketika terjadi kenaikan harga tiket MRT terhadap penurunan jumlah penumpang Transjakarta melalui pendekatan elastisitas harga silang. Pengujian hubungan tersebut dilakukan menggunakan data harian di tingkat halte melalui metode regresi data panel dengan pendekatan Model Fixed Effect. Hasil estimasi menunjukkan bahwa keberadaan MRTberhubungan dengan peningkatan jumlah penumpang Transjakarta sebesar 36,5 persen pada halte Transjakarta yang berada dalamradius 250 meter terhadap stasiun MRT. Namun, penelitian ini belum menemukan cukup bukti adanya hubungan komplementerterkait kenaikan harga tiket MRT terhadap penurunan jumlah penumpang Transjakarta.Kata kunci: elastisitas harga silang, fixed effect, Mass Rapid Transit (MRT), Transjakarta, transportasi